1985
DOI: 10.1136/adc.60.2.110
|View full text |Cite
|
Sign up to set email alerts
|

Cytochemical bioassay of parathyroid hormone in maternal and cord blood.

Abstract: SUMMARY Parathyroid hormone and calcium were measured in plasma taken from pregnant women at term and from the umbilical veins of their infants at birth. Three assays were used to measure parathyroid hormone, a cytochemical bioassay of bioactivity and two immunoradiometric assays, one specific for the amino terminus, the other specific for the carboxy terminus of the parathyroid hormone molecule.Plasma calcium was significantly higher in the infants than in the mothers. Maternal parathyroid hormone bioactivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(31 citation statements)
references
References 36 publications
2
29
0
Order By: Relevance
“…This is in line with the study of Bowyer et al 41 Seki et al 42 found a significantly lower PTH level in cord blood compared with maternal blood at birth, and this was in accordance with the results of Allgrove et al 43 who found low PTH levels in cord blood. They supported the contention that PTH secretion is suppressed by hypercalcemia in late fetal life, and thus Seki et al 42 suggest that stimulation of the placental calcium pump by PTHrP may be operative in humans, leading to low cord blood PTH at birth.…”
Section: Maternal and Infant Vitamin D Status S Vij Streym Et Alsupporting
confidence: 82%
“…This is in line with the study of Bowyer et al 41 Seki et al 42 found a significantly lower PTH level in cord blood compared with maternal blood at birth, and this was in accordance with the results of Allgrove et al 43 who found low PTH levels in cord blood. They supported the contention that PTH secretion is suppressed by hypercalcemia in late fetal life, and thus Seki et al 42 suggest that stimulation of the placental calcium pump by PTHrP may be operative in humans, leading to low cord blood PTH at birth.…”
Section: Maternal and Infant Vitamin D Status S Vij Streym Et Alsupporting
confidence: 82%
“…Cytochemical assays have revealed that fetal blood contains high PTH-like bioactivity, which cannot be accounted for by the low immunoreactive levels of PTH (3,20,67). Following the discovery of PTHrP and the development of specific radioimmunoassays for it, studies in fetal pigs (7) and sheep (94,396) determined that high immunoreactive levels of PTHrP correlated closely with, and likely accounted for, the high PTH-like bioactivity in fetal blood.…”
Section: Pthrpmentioning
confidence: 99%
“…6 It has been suggested that this may be driven by parathyroid hormone (PTH); 7 however, more recent studies have shown a signi¢cant decrease in PTH during pregnancy and have suggested the possible involvement of parathyroid hormone -related protein (PTHrP). 8,9 Bone histology suggests an increase in resorption at this time, 10 and this is supported by recent studies of biochemical markers of bone turnover.…”
Section: Introductionmentioning
confidence: 99%